Pemodelan Calponin Ikan Gabus (Channa striata) dengan Phyre2 dan Interaksi dengan Protein Lain - Mirza Maulana Ahmad; Noer Komari (Universitas Lambung Mangkurat, 2022)
Knowledge of the three-dimensional structure of proteins is very important to understand their character and function at the molecular level. Determination of protein structure in the laboratory is expensive and relatively difficult because it requires sophisticated instruments and takes a long time. As an alternative, an in silico approach can be used to predict the three-dimensional structure of proteins, namely the fold recognition method. The purpose of this study was to create a three-dimensional structure model of snakehead fish (Channa striata) calponin protein using the Phyre2 web server. The target protein sequence was obtained from UniProt KB with code K9LH64. The results of the study showed that the template for building the model was the c1wynA code. The results of the model (MP) evaluation obtained a coverage value was 45%, a confidence value was 100%, and an identity value was 69%. Validation of the model (MP) using the PROCHECK program showed the model was in the most favoured residue plot of 82.4%. This model deserves to be used as a model for calponin protein of snakehead fish, because the disallowed area was below 15%. The results of the analysis of interactions with other proteins using STRING-DB obtained the interaction model (MP) with Actin assembly-inducing protein (ACTA2) was 0.791; and Tropomyosin (TPM1) was 0.786. The results of molecular docking using PatchDock obtained the value of Atomic Contact Energy (ACE) for the calponin protein model (MP)-ACTA2 was 372.76 kJ/mol; Calponin model protein (MP)-TPM1 was 406.93 kJ/mol. The interactions that occured in the calponin model (MP)-ACTA2 were hydrogen bonds at residues Gly-41, Glu-60, Arg-64, Arg-66, Pro-67, Gly-68, Lys-71 and hydrophobic bonds at Arg-64, Lys- 71, Lys-72, Ile-73, Va-138. The interactions model of calponin model (MP)-TPM1 were hydrogen bonding at residues Ser-13, Lys-71, Ala-95, Tyr-96, Ser-136, Arg-137, Arg-150 and hydrophobic bonds at residues Leu-12, Ala-14, Lys-71, Ala-95, Val-138, Arg-150, Phe-152. Keywords: fold recognition, Phyre2 , 3D structure protein, calponin, protein-protein interaction